The Results of Research-Experimental Work on the Formation of the Own Style of Music Teaching of the Future Teachers - Naida, Yurii (Pedagogical Discourse, 2014)
This article focuses attention on the formation of the own style of music teaching of the future teachers, namely: the results of experimental work have been offered. It has been carried out during four years in Khmelnytskyi Humanitarian-Pedagogical Academy with the students of the 1–6 years of study of the faculty of Arts. In the article we have practically tested the effectiveness of mastering by the teacher his or her own style of teaching music that can be acquired in the course of professional training, thanks to the direct pedagogical influence. The received results confirmed the effective mastery of the method of forming the own style of music teaching by the future teachers and showed its availability.